Problems and Prospects of Pilgrim Tourism with Special Reference to Sabari Pilgrimage - Joseph, Anthony (Indian Journal of Marketing, 2004)
"The desire to be a pilgrim is deeply rooted in human nature. To stand where those that we revere stood, to see the very sites where they were born and toiled and died, gives us a feeling of mystical contact with them and is a practical expression of our homage. And if the great men of the world have their shrines to which their admirers come from afar; still more do men flock eagerly to those places where they believe, the divine has sanctified the earth" (Runciman 13). Travel for religious purposes has assumed an increasing significance these days. It is a well-established custom in many parts of the world. In the traditional Indian life, people give utmost importance to spiritual matters and they often visit holy places. At the pilgrim centres various rituals are performed and offerings made for the expiation of sins.